Pengelolaan Sampah Organik dengan Bioaktiator Kelompok PUMA (Klepu Mandiri) Desa Sidomulyo Kecamatan Semen Kabupaten Kediri - Yuly Peristiowati; Titik Mariyati (Universitas Nahdlatul Ulama Surabaya, 2022)
Population growth and development in rural and urban areas has resulted in wider and denser residential areas, which can lead to increased human activities so that it can cause waste problems. The waste problem is still a crucial problem in Indonesia. Researchers from the Indonesian Institute of Sciences (LIPI) revealed that one of the factors for increasing the volume of waste is the behavior of the community, which until now the level of awareness of waste is still considered lacking. Sidomulyo Village, Semen District, Kediri Regency is one of the villages that produces a lot of organic waste. In Sidomulyo Village there are nongovernmental organizations engaged in social, economic, and community fields. The institution is called the PUMA Group (Klepu Mandiri). One of the group's activities is the manufacture of bioactivators made from fruit waste, vegetable waste, and beef rumen. The results of the production of this bioactivator have not been utilized. Methods: In this community service activity, master of health students together with lecturers and the PUMA group together educate the surrounding community in the manufacture of bioactivators which are used to accelerate the decomposition of organic waste. Results: The results of the community service activities carried out were the support from the Village Village and village officials and residents who supported the solid waste management strategy in a relatively short time. All elements of society provide adequate equipment and places that can be used to process waste or waste into economic value, thereby increasing the income of residents from the sale of organic fertilizers. Conclusion: After this community service activity was carried out, the people in Sidomulyo village were able to process organic waste independently or in groups with the support of the PUMA Group (Klepu Mandiri) and the full participation of the entire community.